DIAGNOSTIC CRITERIA OF METABOLIC SYNDROME - Olga Leonidovna Moskalenko; Olga Valentinovna Smirnova; Eduard Vilyamovich Kasparov; Olga Isaevna Zaitseva (Siberian Journal of Life Sciences and Agriculture, 2019)
Metabolic syndrome (MS) is a serious medical, social and economic problem. Timely diagnosis of MS, therapy (treatment of obesity, carbohydrate metabolism disorders, arterial hypertension, dyslipidemia) and prevention (control of body weight, determination of body mass index, physical activity and balanced diet) will effectively reduce the risk of cardiovascular complications associated with atherosclerosis.